Impact of livelihood capital endowment on poverty alleviation of households under rural land consolidation. (October 2021) - Wang, Wenxiong; Lan, Yuanqin; Wang, Xu
Abstract: Poverty eradication is the primary goal of equitable and sustainable development and has received extensive attention from the international academic community. Rural land consolidation (RLC) is designed to achieve sustainable land use by combining land system reform and policy innovation; this has become an important means to promote China's poverty alleviation. From the perspective of micro-farmers, this paper takes the Sustainable Livelihood Approach (SLA) to reveal the influence of livelihood capital endowment on households' income growth and poverty alleviation under different modes of RLC. According to the survey data of registered poor households in four counties (cities) of Hubei Province and Guizhou Province, this paper uses fuzzy set qualitative comparative analysis (fsQCA) to empirically study several combinations of initial livelihood capital endowment after the implementation of different modes of RLC. The results show that RLC improves households' initial livelihood capital endowment, reduces the vulnerability of the livelihood, thus promoting the accumulation of households' livelihood capital and the optimization of livelihood strategies and urging households to obtain a sustainable livelihood, so as to contribute to poverty alleviation. Whether in the government-dominated mode area or Public-Private Partnership（PPP）mode area, the five types of livelihood capital endowments of households are interdependent and collectively affect income growth and poverty alleviation. However, the requirements for households' initial livelihood capital endowments are far lower after the implementation of PPP mode RLC than those after the implementation of government-dominated RLC. Based on these findings, this paper presents corresponding policy recommendations to improve the effectiveness of RLC poverty alleviation policy, and also provides China's experience and reference for other developing countries to formulate targeted antipoverty policies. Highlights: Use the Sustainable Livelihood Approach (SLA) to reveal the impact of livelihood capital endowment (LCE) on households' income growth and poverty alleviation under different rural land consolidation (RLC) modes. Apply fsQCA to test characteristics and differences of initial LCE combination after implementation of different RLC modes. Reveal that the dependence of households' income growth and poverty alleviation on initial LCE in PPP mode are far lower than government-dominated mode.